Adsorption tower inner structure - MIN WEIJIE (2016)
The utility model provides an adsorption tower inner structure, includes the tower body, is equipped with the molecular sieve in the tower body, and the tower body bottom is equipped with the air inlet, and the tower body top is equipped with the gas vent, characterized by for uncovered and cooperation have the gland on: uncovered fit in has the petate, and the petate top is equipped with corrosion resistant plate, and corrosion resistant plate opens there is the bleeder vent. This scheme provides an adsorption tower inner structure, sets up corrosion resistant plate played a supporting role, avoids filtering the backing plate and is out of shape. 种吸附塔内部结构，包括塔体，塔体内设有分子筛，塔体底部设有进气口，塔体顶部为敞口并配合有压盖，压盖上设有排气口，其特征是：所述敞口内配合有棕榈垫，棕榈垫上方设有不锈钢板，不锈钢板开有透气孔。该方案提供了种吸附塔内部结构，设置不锈钢板起到支撑作用，避免过滤垫板变形。